Nutritional vulnerability of early zoeal stages of the invasive shrimp Lysmata vittata (Decapoda: Caridea) in the Atlantic Ocean - Barros-Alves, Samara De P.; Almeida, Andréa Santos E [UNESP]; Almeida, Ariádine Cristine De; Costa, Rogério Caetano Da [UNESP]; Alves, Douglas Fernandes Rodrigues (Cambridge University Press (CUP), 2020)
Lysmata vittata is considered an invasive shrimp in the Atlantic Ocean and some characteristics might have contributed to its invasive success, such as its larval nutritional vulnerability during the early stages of development. The objective of this study was to evaluate the early larval stages of the shrimp L. vittata. Ovigerous specimens were captured in an estuarine region of north-eastern Brazil. Zoeae were assigned to two experiments: (1) the point of no return (PNR), consisting of treatments with an increasing number of days of starvation and subsequent days of feeding; and (2) the point of reserve saturation (PRS), consisting of treatments with an increasing number of days of feeding and subsequent days of starvation. Two control groups were considered: continuous starvation (CS) and continuous feeding (CF). Nutritional vulnerability was estimated by the time when 50% of the initially starved larvae (PNR50) lost the ability to moult to the next stage, when 50% of the initially fed larvae (PRS50) were capable of moulting to the next stage. In the CF, the mean development time (±SD) of the larvae that reached stage III was 4.36 ± 0.74 days with a mortality of 70%, and the mean carapace length (±SD) was 0.61 ± 0.04 mm CL. The PNR50 and PRS50 were 2.42 ± 0.14 and 1.32 ± 0.83 days, respectively. The nutritional vulnerability index (PRS50/PNR50 = 0.54) indicates that L. vittata presents intermediate dependence on exogenous food during the early larval stages, which might help our understanding of the invasive potential of this species in the Atlantic Ocean.
Keywords: Invasive species; larval development; Lysmatidae; starvation